2011
DOI: 10.1073/pnas.1018878108
|View full text |Cite
|
Sign up to set email alerts
|

Cross-species infections of cultured cells by hepatitis E virus and discovery of an infectious virus–host recombinant

Abstract: The RNA virus, hepatitis E virus (HEV) is the most or second-most important cause of acute clinical hepatitis in adults throughout much of Asia, the Middle East, and Africa. In these regions it is an important cause of acute liver failure, especially in pregnant women who have a mortality rate of 20–30%. Until recently, hepatitis E was rarely identified in industrialized countries, but Hepatitis E now is reported increasingly throughout Western Europe, some Eastern European countries, and Japan. Most of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
335
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 281 publications
(347 citation statements)
references
References 27 publications
3
335
2
1
Order By: Relevance
“…AF444002, with insertion of an S17 sequence in the hypervariable region) and one the Kernow‐C1 p6, were used to generate HEV in vitro transcripts as described 22, 23, 24. Capping was performed using Ribom7G Cap Analog (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…AF444002, with insertion of an S17 sequence in the hypervariable region) and one the Kernow‐C1 p6, were used to generate HEV in vitro transcripts as described 22, 23, 24. Capping was performed using Ribom7G Cap Analog (Promega, Madison, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The RPS17 insertion mutant was further selected during serial passages of HEV-containing fecal materials in HepG2C3A cells and exhibited an expanded host range, infecting cells from pig, deer, chicken, cat, dog, mouse, and hamster in vitro (26). In the other case, the HVR of HEV had a 117-nucleotide in-frame insertion derived from the human RPS19 gene, inserting amino acids 93 to 132 (25), and the RSP19 insertion bestowed an enhanced cell culture replication efficiency of HEV, although not to the same degree as that with the RPS17 insertion.…”
mentioning
confidence: 99%
“…4 Subsequent analysis showed that the HEV genotype-3 strain recovered from this patient's stool contained an insertion of 58 amino acids from a human ribosomal protein gene, 61 confirming that a human/hepatitis E recombinant virus exists. However, HEV co-infection in patients with HIV is not common and, to date, less than 20 cases have been documented in the literature, and only a handful have had chronic infection, the majority of these cases become cleared of HEV spontaneously.…”
Section: Hev Infection In Hiv Patientsmentioning
confidence: 80%